Penegakan Pelanggaran Kode Etik Profesi Polri - Dilla Hariyanti; Mugiati (Syntax Literate, 2023)
The occurrence of a violation of the police professional code of ethics asa reflection of the behavior and attitudes of Polri members in carrying out their main functions and duties as law enforcement, unprofessional, this will have an impact on the image of the Republic of Indonesia National Police Institute in the eyes of the public. The National Police Institute of the Republic of Indonesia, must take law enforcement action against cases of violations of the police professional code of ethics committed by members of the Indonesian National Police through Police Code of Ethics Commission. This study formulates the problem of a what are the causes of violations of the professional code of ethics by members of the Police? and what are the law enforcement actions for members of the Police who violate the Police's professional code of ethics? This research uses normative method. The results of the research show that the cause of violations of the professional code of ethics committed by members of the Indonesian National Police is due to discretionary actions that are not in accordance with the legal norms and professional ethics of the Police. Any member of the National Police who violates the professional code of ethics will be subject to ethical and administrative sanctions.